Harmonics elimination for DC/DC power supply based on piezoelectric filters - Hasan Ma Almgotir; Enaam A. Khaliq Ali; Wedian H. Abd al ameer; Mustafa A. Fadel Al-Qaisi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This research presents a study, modelling and simulation of the piezoelectric material work as filters (piezoelectric filter) used to eliminate the harmonics in power electronic circuits, high order harmonics are generating due to the high switching frequencies and circuit equipment, detailed simulation is achieved for the piezoelectric filter tested in full-bridge DC/DC converter circuit with resistive load works as dc power supply (12 to 48 volt). As a result, the uses of piezoelectric filters have a great impact on harmonics elimination, which leads to reduce the overall total harmonic distortion leads to increase the efficiency, as well as the output voltage from the dc power supply remain constant by varying the load resistance over a wide range. The dc power supply circuit including the piezoelectric filter has been simulated using PSIM (V9.1) power electronic circuit simulation software.